Statistics - Abadir, Karim M.; Heijmans, Risto D.H.; Magnus Jan R (New York Cambridge, 2019)
Building on the success of Abadir and Magnus' Matrix Algebra in the Econometric Exercises Series, Statistics serves as a bridge between elementary and specialized statistics. Professors Abadir, Heijmans, and Magnus freely use matrix algebra to cover intermediate to advanced material. Each chapter contains a general introduction, followed by a series of connected exercises which build up knowledge systematically.
Keywords: Statistics textbooks; Probabilities textbooks; Mathematical statistics